DNA damage induced Pol eta recruitment takes place independently of the cell cycle phase - Soria, Ramiro Gasto (2009)
When DNA is damaged in cells progressing through S phase, replication blockage can be avoided by TLS (Translesion DNA synthesis). This is an auxiliary replication mechanism that relies on the function of specialized polymerases that accomplish DNA damage bypass. Intriguingly, recent evidence has linked TLS polymerases to processes that can also take place outside S phase such as nucleotide excision repair (NER). Here we show that Pol eta is recruited to UV-induced DNA lesions in cells outside S phase including cells permanently arrested in G(1). This observation was confirmed by different strategies including global UV irradiation, local UV irradiation and local multi-photon laser irradiation of single nuclei in living cells. The potential connection between Pol eta recruitment to DNA lesions outside S phase and NER was further evaluated. Interestingly, the recruitment of Pol eta to damage sites outside S phase did not depend on active NER, as UV-induced focus formation occurred normally in XPA, XPG and XPF deficient fibroblasts. Our data reveals that the re-localization of the TLS polymerase Pol eta to photo-lesions might be temporally and mechanistically uncoupled from replicative DNA synthesis and from DNA damage processing.